THE EFFECT OF AQUEOUS AND ALCOHOLIC EXTRACT OF CYPERUS LONGOUS (CYPERACEAE) AND TOW DRUGS (TINIDAZOLE AND PRAZIQUANTEL) ON KILLING THE PROTOSCOLICES OF ECHINOCOCCUS GRANULOSUS IN VITRO. - Fatin Abdul-Jabbar-Mustafa (Basrah Journal of Veterinary Research)
The main objective of this study was to evaluate the activity of aqueous and alcoholic extracts of Cyperus longous (Rhizomes) on killing the (larval stage) protoscolices of Echinococcus granulosus in vitro compared with the two drugs Tinidazole and Praziquantel using the concentrations (5 , 10 , 15 , 20) % of the plant extracts and (1.25 , 1.8 , 2.5) % for Tinidazole and (0.1 , 0.15 , 0.2) % for Praziquantel respectively. The study shows that the aqueous extract at 20% have showen highest protoscolicidal activity. All the protoscolices were killed in the first day after treatment. While the concentration 5% shows the lowest activity in killing the protoscolices which was in the 6th day , while the time of killing protoscolices was in the 3rd day and 2nd day at the concentration (10 , 15)% respectively. There is no significant differences between aqueous and alcoholic extract of Cyperus longous P< 0.01 , so aqueous extract used in our study because of its lower price and its safety. Tinidazole and Praziquantel have showen the great activity on killing the protoscolices in the ½ an hour and an hour at (2.5 , 0.2) % respectively. The preservative solution ( Hankُ s solution). Keep the protoscolices viable 59% to 21 days.